Solid electrolyte reactor for synergistically removing NOX and VOCs and preparation method

By using a porous structure of LPBxN-SDC electrode in a solid electrolyte reactor, the problems of temperature window mismatch, limited reaction sites and catalyst poisoning in the prior art are solved, and efficient pollutant removal and electrochemical performance improvement are achieved.

CN119701594AActive Publication Date: 2025-03-28ZHENGZHOU UNIV
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411915997.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-24
Publication Date
2025-03-28
Estimated Expiration
2044-12-24

AI Technical Summary

Technical Problem

The prior art has problems such as temperature window mismatch, limited reaction sites, and easy catalyst poisoning when synergistically removing NOx and VOCs.

Method used

Using a solid electrolyte reactor, including a cathode and anode with a porous structure, both the cathode and the anode contain La0.5Pr1.5-xBaxNiO4 (LPBxN) and Ce0.8Sm0.2O1.9 (SDC) materials, the electrode slurry is prepared by screen printing technology and attached to the solid electrolyte substrate.

Benefits of technology

This method effectively avoids the problems of temperature window mismatch, limited reaction sites and catalyst poisoning, improves the removal rate and current density of NOx and VOCs, and reduces the polarization resistance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119701594A_ABST
    Figure CN119701594A_ABST
Patent Text Reader

Abstract

The invention relates to a solid electrolyte reactor for synergistically removing NOX and VOCs (Volatile Organic Compounds). The reactor comprises a solid electrolyte substrate, a cathode located on one side face of the solid electrolyte substrate and an anode located on the other side face of the solid electrolyte substrate, and the cathode and the anode are made of the same material. The cathode and the anode are both of a porous structure, the cathode and the anode both comprise La < 0.5 > Pr < 1.5-x > BaxNiO4 (LPBxN) and Ce < 0.8 > Sm < 0.2 > O < 1.9 > (SDC), and the Ce < 0.8 > Sm < 0.2 > O < 1.9 > (SDC) accounts for 30%-40% of the total mass of the cathode and the anode. According to the method, a reducing agent does not need to be added, and the problems that when NOx and VOCs are synergistically removed through a traditional NH3-SCR method, temperature windows are not matched, reaction sites are limited, and a catalyst is prone to poisoning can be effectively solved. And meanwhile, the VOCs can consume redundant O2 in the gas, so that the competitive reduction of O2 and NOX at the cathode is reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of electrochemical degradation of gaseous pollutants, and in particular to a method for synergistically removing NO X Solid electrolyte reactor for treating VOCs and preparation method thereof. Background Art

[0002] Nitrogen oxides (NOx) and volatile organic compounds (VOCs) are two important pollutants in the atmosphere, which can cause serious harm to the ecological environment and public health. In addition, fine particulate matter (PM 2.5 ) and ozone (O3) synergistic control has become the key to continuously improving air quality in my country, and NOx and VOCs are common precursors of both, so achieving synergistic reduction of NOx and VOCs is the key to achieving PM 2.5 The most effective means of collaborative control with O3.

[0003] Some studies in recent years have shown that synergistic control of VOCs based on NH3-SCR denitrification is considered to be one of the efficient and economical technical options. However, this method generally has the following technical problems: (1) The temperature windows of NOx reduction reaction and VOCs oxidation reaction do not match, and a catalyst with a suitable temperature window needs to be developed; (2) NOx will compete with VOCs for the limited reaction sites on a single catalyst, thereby reducing the pollutant removal performance; (3) Complex flue gas environment can lead to catalyst poisoning and even the production of various by-products, causing secondary pollution. Summary of the invention

[0004] The object of the present invention is to provide a method for synergistically removing NO X A solid electrolyte reactor for removing NOx and VOCs is provided to solve the technical problems of temperature window mismatch, limited reaction sites, and easy catalyst poisoning when the traditional NH3-SCR method is used in the prior art to synergistically remove NOx and VOCs; at the same time, the purpose of the present invention is also to provide a method for preparing the above-mentioned solid electrolyte reactor.

[0005] To achieve the above object, the present invention provides a method for synergistically removing NO X The solid electrolyte reactor for VOCs and NOx adopts the following technical solutions: a synergistic removal of NO X A solid electrolyte reactor for treating VOCs, comprising a solid electrolyte substrate, a cathode located on one side of the solid electrolyte substrate, and an anode located on the other side of the solid electrolyte substrate, wherein the cathode and the anode are made of the same material; both the cathode and the anode are porous structures, and both the cathode and the anode contain La 0.5 Pr 1.5-x Ba x NiO4(LPB x N) and Ce 0.8 Sm 0.2 O1.9 (SDC), where Ce 0.8 Sm 0.2 O 1.9 (SDC) accounts for 30%-40% of the total mass of the two.

[0006] The cathode and the anode are both made of La 0.5 Pr 1.5-x Ba x NiO4(LPB x N) powder and Ce 0.8 Sm 0.2 O 1.9 The SDC powder and the binder are made into electrode slurry, and the electrode slurry is made on the corresponding side of the solid electrolyte substrate by screen printing.

[0007] La 0.5 P r1.5-x Ba x NiO4(LPB x N) Powder was prepared by the following method:

[0008] 1) dissolving La(NO3)3·6H2O, PrN3O9·6H2O, Ba(NO3)2 and Ni(NO3)2·6H2O in distilled water, and controlling the molar ratio of La, Pr, Ba and Ni metal ions to be 0.5:1.5-x:x:1;

[0009] 2) adding citric acid and ethylenediaminetetraacetic acid to the above solution, controlling the molar ratio of total metal ion: ethylenediaminetetraacetic acid: citric acid = 1:1:1.5;

[0010] 3) heating in a water bath, adding ammonia water to the solution of step 2) to adjust the pH to 6-8, stirring, and obtaining a wet gel;

[0011] 4) drying the wet gel in step 3) to obtain a loose and porous dry gel;

[0012] 5) Calcine the dry gel to obtain La 0.5 Pr 1.5-x Ba x NiO4(LPB x N) powder.

[0013] Ce 0.8 Sm 0.2 O 1.9 (SDC) powder was prepared by the following method:

[0014] 1) Dissolve Ce(NO3)3·6H2O and Sm(NO3)3·6H2O in distilled water, and control the molar ratio of Ce and Sm metal ions to be 8:2;

[0015] 2) adding citric acid and ethylenediaminetetraacetic acid to the above solution, controlling the molar ratio of total metal ion: ethylenediaminetetraacetic acid: citric acid = 1:1:1.5;

[0016] 3) heating in a water bath, adding ammonia water to the solution to adjust the pH to 6-8, stirring, and obtaining a wet gel;

[0017] 4) drying the wet gel in step 3) to obtain a loose and porous dry gel;

[0018] 5) Calcine the dry gel to obtain Ce 0.8 Sm 0.2 O 1.9 (SDC) powder.

[0019] The solid electrolyte substrate adopts a yttrium stabilized zirconia (YSZ) substrate.

[0020] The preparation method of the solid electrolyte reactor of the present invention adopts the following technical scheme: a synergistic removal of NO as claimed in claim 1 X A method for preparing a solid electrolyte reactor for treating VOCs comprises the following steps:

[0021] 1) Preparation of solid electrolyte substrate, La 0.5 Pr 1.5-x Ba x NiO4(LPB x N) powder and Ce 0.8 Sm 0.2 O 1.9 (SDC) powder;

[0022] 2) preparing electrode slurry from the metal oxide powder in step 1);

[0023] 3) The electrode slurry in step 2) is made into a cathode attached to one side of the solid electrolyte substrate and an anode attached to the other side by screen printing based on the solid electrolyte substrate to obtain a solid electrolyte reactor.

[0024] In step 1), the solid electrolyte substrate is prepared by the following method: yttrium stabilized zirconia (YSZ) powder is taken, dry-pressed at a pressure of 180-200 MPa to form an electrolyte green body, and then calcined to obtain a solid electrolyte substrate.

[0025] In step 1), La 0.5 Pr 1.5-x Ba x NiO4(LPB x N) Powder was prepared by the following method:

[0026] 1) dissolving La(NO3)3·6H2O, PrN3O9·6H2O, Ba(NO3)2 and Ni(NO3)2·6H2O in distilled water, and controlling the molar ratio of La, Pr, Ba and Ni metal ions to be 0.5:1.5-x:x:1;

[0027] 2) adding citric acid and ethylenediaminetetraacetic acid to the above solution, controlling the molar ratio of total metal ion: ethylenediaminetetraacetic acid: citric acid = 1:1:1.5;

[0028] 3) heating in a water bath, adding ammonia water to the solution of step 2) to adjust the pH to 6-8, stirring, and obtaining a wet gel;

[0029] 4) drying the wet gel in step 3) to obtain a loose and porous dry gel;

[0030] 5) Calcine the dry gel to obtain La 0.5 Pr 1.5-x Ba x NiO4(LPB x N) powder.

[0031] In step 1), Ce 0.8 Sm 0.2 O 1.9 (SDC) powder was prepared by the following method:

[0032] 1) Dissolve Ce(NO3)3·6H2O and Sm(NO3)3·6H2O in distilled water, and control the molar ratio of Ce and Sm metal ions to be 8:2;

[0033] 2) adding citric acid and ethylenediaminetetraacetic acid to the above solution, controlling the molar ratio of total metal ion: ethylenediaminetetraacetic acid: citric acid = 1:1:1.5;

[0034] 3) heating in a water bath, adding ammonia water to the solution to adjust the pH to 6-8, stirring, and obtaining a wet gel;

[0035] 4) drying the wet gel in step 3) to obtain a loose and porous dry gel;

[0036] 5) Calcine the dry gel to obtain Ce 0.8 Sm 0.2 O 1.9 (SDC) powder.

[0037] In step 2), the electrode slurry is prepared by the following method: taking La 0.5 Pr 1.5-x Ba x NiO4(LPB x N) powder and Ce 0.8 Sm0.2 O 1.9 (SDC) powder, Ce 0.8 Sm 0.2 O 1.9 The (SDC) powder accounts for 30-40% of the total mass of the two. After grinding, a binder is added. The mass ratio of the total amount of metal oxide powder to the binder is 1:1.5. Grinding is continued to obtain an electrode slurry.

[0038] Beneficial effects of the present invention: The present invention constructs a method based on LPB x Electrochemical reactor with N-SDC electrode. The electrode has good porosity and large specific surface area, which can provide sufficient active adsorption sites for catalytic reactions. Barium doping effectively improves the pollutant removal rate and current density of the electrode and reduces polarization resistance. LPB x As a RP-type perovskite powder, its unique AO rock salt layer enables it to accommodate additional interstitial oxygen, and gives the material a higher oxygen surface exchange coefficient and bulk diffusion coefficient, as well as sufficient oxygen ion conductivity. SDC powder has a higher oxygen ion conductivity and good chemical matching with the electrolyte. x Adsorbed on the cathode and obtained electrons to be reduced to N2 and produce O 2- Ions, O 2- The ions are transferred to the anode through the solid electrolyte and react with the VOCs adsorbed on the anode to generate CO2 and H2O. This method does not require the addition of a reducing agent and can effectively avoid the problems of temperature window mismatch, limited reaction sites, and easy catalyst poisoning when the traditional NH3-SCR method is used to remove NOx and VOCs in a coordinated manner. At the same time, VOCs can consume excess O2 in the gas and reduce the competitive reduction of O2 and NOx at the cathode. BRIEF DESCRIPTION OF THE DRAWINGS

[0039] Figure 1 It is a synergistic removal of NO X Schematic diagram of the working principle of the solid electrolyte reactor for evaporating VOCs;

[0040] Figure 2 It is a synergistic removal of NO X Schematic diagram of the structure of the solid electrolyte reactor for evaporating VOCs;

[0041] Figure 3 It is a schematic diagram of the structure of the NOx and VOCs synergistic removal reaction device;

[0042] Figure 4 The LPN-SDC reactor and the LPB in Example 1 0.1 XRD spectrum of the electrode of N-SDC reactor;

[0043] Figure 5 The LPN-SDC reactor and the LPB in Example 1 0.1 SEM image of the electrodes of the N-SDC reactor;

[0044] Figure 6 It is LPB in the first embodiment 0.1 Cross-sectional SEM image of the N-SDC reactor;

[0045] Figure 7 The LPN-SDC reactor and the LPB in Example 1 0.1 (a) NO conversion and (b) propane conversion of the N-SDC reactor at 750 °C in 1000 ppm NO and 2000 ppm C3H8 environments;

[0046] Figure 8 The LPN-SDC reactor and the LPB in Example 1 0.1 (a) NO conversion and (b) propane conversion of the N-SDC reactor at 750 °C in an environment of 1000 ppm NO, 2000 ppm C3H8 and 2.0 vol% O2;

[0047] Fig. 9 The LPN-SDC reactor and the LPB in Example 1 0.1 AC impedance spectra of the N-SDC reactor at 750 °C in (a) 1000 ppm NO and 2000 ppm C3H8 environment and (b) 1000 ppm NO, 2000 ppm C3H8 and 2.0 vol% O2 environment;

[0048] Fig.10 The LPN-SDC reactor and the LPB in Example 1 0.1 IV curves of the N-SDC reactor at 750 °C in (a) 1000 ppm NO and 2000 ppm C3H8 environment and (b) 1000 ppm NO, 2000 ppm C3H8 and 2.0 vol% O2 environment;

[0049] Description of reference numerals: 1. electrode; 2. solid electrolyte substrate; 3. LPB x N; 4. SDC; 5. Outer wall of reaction chamber; 6. Corundum tube; 7. Gas outlet; 8. Gas inlet; 9. Solid electrolyte reactor; 10. Solid electrolyte substrate; 11. Anode; 12. Cathode; 13. DC power supply; 14. Silver wire; 15. Temperature controller; 16. Thermocouple; 17. Heating element. DETAILED DESCRIPTION

[0050] A synergistic removal of NO by the present invention X and solid electrolyte reactors for VOCs, such as Figure 1 and 2 As shown, it includes a solid electrolyte substrate 2, a cathode located on one side of the solid electrolyte substrate and an anode 1 located on the other side of the solid electrolyte substrate. The cathode and the anode are made of the same material, both of which are porous structures, and both of which include La 0.5 Pr 1.5- x Ba x NiO4(LPB x N) and Ce 0.8 Sm 0.2 O 1.9 (SDC), where x represents the doping amount of Ba ions, specifically the amount of Ba ions replacing Pr ions, and x is less than or equal to 0.2. For example, x = 0, then the chemical formula is La 0.5 Pr 1.5 NiO4, which means that there is no Ba ion replacing the Pr position, and it is in an undoped state; if x = 0.1, the chemical formula is La 0.5 Pr 1.4 Ba 0.1 NiO4 means that in each chemical formula unit, 0.1 mole of Pr is replaced by Ba. 0.5 Pr 1.5-x Ba x NiO4(LPB x N) and Ce 0.8 Sm 0.2 O 1.9 The reference numerals of (SDC) are 3 and 4 respectively. The solid electrolyte substrate 2 uses a yttria-stabilized zirconia (YSZ) substrate.

[0051] The solid electrolyte reactor of the present invention synergistically removes NO X The principle of VOCs is as follows: Figure 1 As shown in the figure, taking NO and propane (C3H8) as an example, NO is adsorbed on the cathode and obtains electrons to be reduced to N2 and produce O 2- Ions, O 2- The ions are transferred to the anode through the solid electrolyte and react with C3H8 adsorbed on the anode to generate CO2 and H2O. This method does not require the addition of a reducing agent and can effectively avoid the problems of temperature window mismatch, limited reaction sites, and easy catalyst poisoning when the traditional NH3-SCR method is used to remove NOx and VOCs in a coordinated manner. At the same time, VOCs can consume excess O2 in the flue gas, reducing the cathode O2 and NO x Competitive reduction.

[0052] The preparation method of the solid electrolyte reactor is described in detail below with reference to an embodiment:

[0053] Embodiment 1

[0054] 1) Preparation of solid electrolyte substrate, La 0.5 Pr 1.5-x Ba x NiO4(LPB x N) powder and Ce 0.8 Sm 0.2 O 1.9 (SDC) powder.

[0055] Preparation of solid electrolyte substrate: 200 mg of yttrium-stabilized zirconia (YSZ) powder was dry-pressed at a pressure of 200 MPa to form an electrolyte green body, which was then placed in a muffle furnace and calcined at 1400°C for 4 hours to obtain a solid electrolyte substrate with a diameter of about 1 cm and a thickness of about 330 μm.

[0056] La 0.5 Pr 1.5-x Ba x NiO4(LPB x N) Preparation of powder:

[0057] In a beaker, La(NO3)3·6H2O, PrN3O9·6H2O, Ba(NO3)2 and Ni(NO3)2·6H2O were dissolved in distilled water, and the molar ratio of La, Pr, Ba and Ni metal ions was controlled to be 0.5:1.4:0.1:1. Citric acid and ethylenediaminetetraacetic acid were added to the above solution, and the molar ratio was controlled to be the total amount of metal ions: ethylenediaminetetraacetic acid: citric acid = 1:1:1.5. The beaker was placed in an 80°C water bath and heated continuously, and ammonia water was added to the beaker to adjust the pH to 7, and stirred continuously until the solution became a viscous light blue wet gel. The wet gel in the beaker was transferred to a porcelain crucible and placed in a blast drying oven, the temperature was set to 160°C, and the dry gel was dried continuously to obtain a loose and porous dry gel. The dry gel was placed in a muffle furnace and calcined at 950°C for 5h, and the black La was obtained by grinding. 0.5 Pr 1.4 Ba 0.1 NiO4(LPB 0.1 N) powder.

[0058] Ce 0.8 Sm 0.2 O 1.9 Preparation of (SDC) powder:

[0059] In a beaker, dissolve Ce(NO3)3·6H2O and Sm(NO3)3·6H2O in distilled water, and control the molar ratio of Ce and Sm metal ions to 8:2. Add citric acid and ethylenediaminetetraacetic acid to the above solution, and control the molar ratio to be the total amount of metal ions: ethylenediaminetetraacetic acid: citric acid = 1:1:1.5. Place the beaker in an 80°C water bath crucible and continue to heat it, and add ammonia water to the solution to adjust the pH to 7, and continue magnetic stirring until the solution becomes a viscous wet gel. Transfer the wet gel in the beaker to a porcelain crucible, and place it in a blast drying oven, set the temperature to 160°C, and continue drying to obtain a loose and porous dry gel. Transfer the dry gel to a muffle furnace and calcine it at 900°C for 3h to obtain Ce 0.8 Sm 0.2 O 1.9 (SDC) powder.

[0060] 2) The metal oxide powder in step 1) is used to prepare electrode slurry.

[0061] Weigh La at a mass ratio of 0.65:0.35 0.5 Pr 1.4 Ba 0.1 NiO4(LPB 0.1 N) powder and Ce 0.8 Sm 0.2 O 1.9 (SDC) powder in a mortar, i.e. Ce 0.8 Sm 0.2 O 1.9 The mass ratio of SDC to the two is 35%. Then grind for 30 minutes, then add pineol as a binder, the mass ratio of the mixed powder to pineol is controlled at 1:1.5, and continue grinding until a uniformly mixed and viscous electrode slurry is obtained.

[0062] 3) The electrode slurry in step 2) is made into a cathode attached to one side of the solid electrolyte substrate and an anode attached to the other side by screen printing based on the solid electrolyte substrate to obtain a solid electrolyte reactor.

[0063] Specifically, the prepared electrode slurry was screen-printed on one side of the solid electrolyte substrate and dried in an oven at 140°C. After being taken out, the electrode slurry was attached to the other side of the solid electrolyte substrate in the same way and dried in an oven at 140°C. Finally, it was calcined in a muffle furnace at 1050°C for 4 hours to obtain a complete solid electrolyte reactor.

[0064] Embodiment 2

[0065] 1) Preparation of solid electrolyte substrate, La 0.5 Pr 1.5-x Ba xNiO4(LPB x N) powder and Ce 0.8 Sm 0.2 O 1.9 (SDC) powder.

[0066] Preparation of solid electrolyte substrate: 200 mg of yttrium-stabilized zirconia (YSZ) powder was dry-pressed at a pressure of 180 MPa to form an electrolyte green body, which was then placed in a muffle furnace and calcined at 1400°C for 4 hours to obtain a solid electrolyte substrate with a diameter of about 1 cm and a thickness of about 330 μm.

[0067] La 0.5 Pr 1.5-x Ba x NiO4(LPB x N) Preparation of powder:

[0068] In a beaker, La(NO3)3·6H2O, PrN3O9·6H2O, Ba(NO3)2 and Ni(NO3)2·6H2O were dissolved in distilled water, and the molar ratio of La, Pr, Ba and Ni metal ions was controlled to be 0.5:1.4:0.1:1. Citric acid and ethylenediaminetetraacetic acid were added to the above solution, and the molar ratio was controlled to be the total amount of metal ions: ethylenediaminetetraacetic acid: citric acid = 1:1:1.5. The beaker was placed in an 80°C water bath and heated continuously, and ammonia water was added to the beaker to adjust the pH to 6, and stirred continuously until the solution became a viscous light blue wet gel. The wet gel in the beaker was transferred to a porcelain crucible and placed in a blast drying oven, the temperature was set to 160°C, and the dry gel was dried continuously to obtain a loose and porous dry gel. The dry gel was placed in a muffle furnace and calcined at 950°C for 5h, and the black La was obtained by grinding. 0.5 Pr 1.4 Ba 0.1 NiO4(LPB 0.1 N) powder.

[0069] Ce 0.8 Sm 0.2 O 1.9 Preparation of (SDC) powder:

[0070] In a beaker, dissolve Ce(NO3)3·6H2O and Sm(NO3)3·6H2O in distilled water, and control the molar ratio of Ce and Sm metal ions to be 8:2. Add citric acid and ethylenediaminetetraacetic acid to the above solution, and control the molar ratio to be the total amount of metal ions: ethylenediaminetetraacetic acid: citric acid = 1:1:1.5. Place the beaker in an 80°C water bath crucible and continue to heat it, and add ammonia water to the solution to adjust the pH to 6, and continue magnetic stirring until the solution becomes a viscous wet gel. Transfer the wet gel in the beaker to a porcelain crucible, and place it in a blast drying oven, set the temperature to 160°C, and continue drying to obtain a loose and porous dry gel. Transfer the dry gel to a muffle furnace and calcine it at 900°C for 3h to obtain Ce 0.8 Sm 0.2 O 1.9 (SDC) powder.

[0071] 2) The metal oxide powder in step 1) is used to prepare electrode slurry.

[0072] Weigh La at a mass ratio of 0.6:0.4 0.5 Pr 1.4 Ba 0.1 NiO4(LPB 0.1 N) powder and Ce 0.8 Sm 0.2 O 1.9 (SDC) powder in a mortar, i.e. Ce 0.8 Sm 0.2 O 1.9 The mass ratio of SDC to the two is 40%. Grind for 30 minutes, then add pineol as a binder, the mass ratio of the mixed powder to pineol is controlled at 1:1.5, and continue grinding until a uniformly mixed and viscous electrode slurry is obtained.

[0073] 3) The electrode slurry in step 2) is made into a cathode attached to one side of the solid electrolyte substrate and an anode attached to the other side by screen printing based on the solid electrolyte substrate to obtain a solid electrolyte reactor.

[0074] Specifically, the prepared electrode slurry was screen-printed on one side of the solid electrolyte substrate and dried in an oven at 140°C. After being taken out, the electrode slurry was attached to the other side of the solid electrolyte substrate in the same way and dried in an oven at 140°C. Finally, it was calcined in a muffle furnace at 1050°C for 4 hours to obtain a complete solid electrolyte reactor.

[0075] Embodiment 3

[0076] 1) Preparation of solid electrolyte substrate, La 0.5 Pr 1.5-x Ba xNiO4(LPB x N) powder and Ce 0.8 Sm 0.2 O 1.9 (SDC) powder.

[0077] Preparation of solid electrolyte substrate: 200 mg of yttrium-stabilized zirconia (YSZ) powder was dry-pressed at a pressure of 200 MPa to form an electrolyte green body, which was then placed in a muffle furnace and calcined at 1400°C for 4 hours to obtain a solid electrolyte substrate with a diameter of about 1 cm and a thickness of about 330 μm.

[0078] La 0.5 Pr 1.5-x Ba x NiO4(LPB x N) Preparation of powder:

[0079] In a beaker, La(NO3)3·6H2O, PrN3O9·6H2O, Ba(NO3)2 and Ni(NO3)2·6H2O were dissolved in distilled water, and the molar ratio of La, Pr, Ba and Ni metal ions was controlled to be 0.5:1.4:0.1:1. Citric acid and ethylenediaminetetraacetic acid were added to the above solution, and the molar ratio was controlled to be the total amount of metal ions: ethylenediaminetetraacetic acid: citric acid = 1:1:1.5. The beaker was placed in an 80°C water bath and heated continuously, and ammonia water was added to the beaker to adjust the pH to 8, and stirred continuously until the solution became a viscous light blue wet gel. The wet gel in the beaker was transferred to a porcelain crucible and placed in a blast drying oven, the temperature was set to 160°C, and the dry gel was dried continuously to obtain a loose and porous dry gel. The dry gel was placed in a muffle furnace and calcined at 950°C for 5h, and the black La was obtained by grinding. 0.5 Pr 1.4 Ba 0.1 NiO4(LPB 0.1 N) powder.

[0080] Ce 0.8 Sm 0.2 O 1.9 Preparation of (SDC) powder:

[0081] In a beaker, dissolve Ce(NO3)3·6H2O and Sm(NO3)3·6H2O in distilled water, and control the molar ratio of Ce and Sm metal ions to be 8:2. Add citric acid and ethylenediaminetetraacetic acid to the above solution, and control the molar ratio to be the total amount of metal ions: ethylenediaminetetraacetic acid: citric acid = 1:1:1.5. Place the beaker in an 80°C water bath crucible and continue to heat it, and add ammonia water to the solution to adjust the pH to 8, and continue to stir magnetically until the solution becomes a viscous wet gel. Transfer the wet gel in the beaker to a porcelain crucible, and place it in a blast drying oven, set the temperature to 160°C, and continue to dry to obtain a loose and porous dry gel. Transfer the dry gel to a muffle furnace and calcine it at 900°C for 3h to obtain Ce 0.8 Sm 0.2 O 1.9 (SDC) powder.

[0082] 2) The metal oxide powder in step 1) is used to prepare electrode slurry.

[0083] Weigh La at a mass ratio of 0.7:0.3 0.5 Pr 1.4 Ba 0.1 NiO4(LPB 0.1 N) powder and Ce 0.8 Sm 0.2 O 1.9 (SDC) powder in a mortar, i.e. Ce 0.8 Sm 0.2 O 1.9 The mass ratio of SDC to the two is 30%. Grind for 30 minutes, then add pineol as a binder, the mass ratio of the mixed powder to pineol is controlled at 1:1.5, and continue grinding until a uniformly mixed and viscous electrode slurry is obtained.

[0084] 3) The electrode slurry in step 2) is made into a cathode attached to one side of the solid electrolyte substrate and an anode attached to the other side by screen printing based on the solid electrolyte substrate to obtain a solid electrolyte reactor.

[0085] Specifically, the prepared electrode slurry was screen-printed on one side of the solid electrolyte substrate and dried in an oven at 140°C. After being taken out, the electrode slurry was attached to the other side of the solid electrolyte substrate in the same way and dried in an oven at 140°C. Finally, it was calcined in a muffle furnace at 1050°C for 4 hours to obtain a complete solid electrolyte reactor.

[0086] Embodiment 4

[0087] 1) Preparation of solid electrolyte substrate, La 0.5 Pr 1.5-x Ba xNiO4(LPB x N) powder and Ce 0.8 Sm 0.2 O 1.9 (SDC) powder.

[0088] Preparation of solid electrolyte substrate: 200 mg of yttrium-stabilized zirconia (YSZ) powder was dry-pressed at a pressure of 200 MPa to form an electrolyte green body, which was then placed in a muffle furnace and calcined at 1400°C for 4 hours to obtain a solid electrolyte substrate with a diameter of about 1 cm and a thickness of about 330 μm.

[0089] La 0.5 Pr 1.5-x Ba x NiO4(LPB x N) Preparation of powder:

[0090] In a beaker, La(NO3)3·6H2O, PrN3O9·6H2O, Ba(NO3)2 and Ni(NO3)2·6H2O were dissolved in distilled water, and the molar ratio of La, Pr, Ba and Ni metal ions was controlled to be 0.5:1.3:0.2:1. Citric acid and ethylenediaminetetraacetic acid were added to the above solution, and the molar ratio was controlled to be the total amount of metal ions: ethylenediaminetetraacetic acid: citric acid = 1:1:1.5. The beaker was placed in an 80°C water bath and heated continuously, and ammonia water was added to the beaker to adjust the pH to 7, and stirred continuously until the solution became a viscous light blue wet gel. The wet gel in the beaker was transferred to a porcelain crucible and placed in a blast drying oven, the temperature was set to 160°C, and the dry gel was dried continuously to obtain a loose and porous dry gel. The dry gel was placed in a muffle furnace and calcined at 950°C for 5h, and the black La was obtained by grinding. 0.5 Pr 1.3 Ba 0.2 NiO4(LPB 0.2 N) powder.

[0091] Ce 0.8 Sm 0.2 O 1.9 Preparation of (SDC) powder:

[0092] In a beaker, dissolve Ce(NO3)3·6H2O and Sm(NO3)3·6H2O in distilled water, and control the molar ratio of Ce and Sm metal ions to 8:2. Add citric acid and ethylenediaminetetraacetic acid to the above solution, and control the molar ratio to be the total amount of metal ions: ethylenediaminetetraacetic acid: citric acid = 1:1:1.5. Place the beaker in an 80°C water bath crucible and continue to heat it, and add ammonia water to the solution to adjust the pH to 7, and continue magnetic stirring until the solution becomes a viscous wet gel. Transfer the wet gel in the beaker to a porcelain crucible, and place it in a blast drying oven, set the temperature to 160°C, and continue drying to obtain a loose and porous dry gel. Transfer the dry gel to a muffle furnace and calcine it at 900°C for 3h to obtain Ce 0.8 Sm 0.2 O 1.9 (SDC) powder.

[0093] 2) The metal oxide powder in step 1) is used to prepare electrode slurry.

[0094] Weigh La at a mass ratio of 0.65:0.35 0.5 Pr 1.3 Ba 0.2 NiO4(LPB 0.2 N) powder and Ce 0.8 Sm 0.2 O 1.9 (SDC) powder in a mortar, i.e. Ce 0.8 Sm 0.2 O 1.9 The mass ratio of SDC to the two is 35%. Then grind for 30 minutes, then add pineol as a binder, the mass ratio of the mixed powder to pineol is controlled at 1:1.5, and continue grinding until a uniformly mixed and viscous electrode slurry is obtained.

[0095] 3) The electrode slurry in step 2) is made into a cathode attached to one side of the solid electrolyte substrate and an anode attached to the other side by screen printing based on the solid electrolyte substrate to obtain a solid electrolyte reactor.

[0096] Specifically, the prepared electrode slurry was screen-printed on one side of the solid electrolyte substrate and dried in an oven at 140°C. After being taken out, the electrode slurry was attached to the other side of the solid electrolyte substrate in the same way and dried in an oven at 140°C. Finally, it was calcined in a muffle furnace at 1050°C for 4 hours to obtain a complete solid electrolyte reactor.

[0097] Comparative Example

[0098] The La:Pr:Ba:Ni metal ion molar ratio in Experimental Example 1 was modified to 0.5:1.5:0:1, that is, no barium doping was included. The other conditions were the same as those in Example 1, and the obtained solid electrolyte reactor was recorded as LPN-SDC reactor.

[0099] In order to verify the effect of the present invention, the product (LPB 0.1 N-SDC reactor) and the comparative product (LPN-SDC reactor) were tested, wherein: the electrodes of the LPN-SDC reactor and the LPB 0.1 The XRD spectrum of the electrode of the N-SDC reactor is shown in Figure 4 As shown. Prepared LPB x N powder shows a single RP phase with no impurity peaks. Ba doping causes the material to transform from an orthorhombic system to a tetragonal system, increasing the symmetry of the crystal structure. Electrodes and LPB of the LPN-SDC reactor 0.1 SEM images of the electrodes of the N-SDC reactor, such as Figure 5 As shown, the electrode shows a porous structure, which is beneficial to the adsorption and diffusion process of gases on the electrode. 0.1 The cross-sectional SEM image of the N-SDC reactor is shown in Figure 2. Figure 6 As shown, the electrode presents a loose and porous structure, while the electrolyte presents a dense structure, and their thicknesses are approximately 7.4 μm and 333 μm, respectively.

[0100] Build NO x And VOCs collaborative removal reaction device: The gas reaction device includes an outer wall 5 of the reaction chamber, and a corundum tube 6 is arranged inside the outer wall of the reaction chamber. The inner cavity of the corundum tube forms a gas reaction chamber, and the gas reaction chamber has an air inlet 8 and an air outlet 7. The gas reaction device also includes a DC power supply 13 and a heating device. The solid electrolyte reactor 9 is placed vertically in the gas reaction chamber, and the cathode and anode are connected to the DC power supply 13 through conductive silver glue and silver wire 14. The heating device provides the required temperature for the gas reaction chamber, and the temperature is controlled by the temperature controller 15, specifically using a heating rod 17 arranged in the corundum tube 6. A thermocouple 16 is arranged inside the gas reaction chamber, and the thermocouple 16 and the heating element 17 are both connected to the temperature controller 15, and can provide real-time feedback to adjust the temperature in the gas reaction chamber. Taking NO and C3H8 gases as examples, taking the LPN-SDC reactor and LPB 0.1 The N-SDC reactor was tested for performance. Details are as follows:

[0101] 1000ppm NO and 2000ppm C3H8 gas were introduced into the reaction chamber, and the total gas flow rate was controlled to be 50mL / min. The temperature was raised to 750℃ at a rate of 5℃ / min by the temperature controller. Then a certain voltage was applied to both ends of the battery through a DC power supply. The inlet and outlet gas concentrations of the reaction chamber were tested using a flue gas analyzer (AW-T6). The test results are shown in Figure 7 As shown, at 0.8V, LPB 0.1 The NO conversion rate of the N-SDC reactor reached 89.5%, which was higher than 87.1% of the LPN-SDC reactor. 0.1 The propane conversion of the N-SDC reactor was 77.9%, slightly higher than 77.0% for the LPN-SDC reactor.

[0102] Electrochemical performance test: The electrochemical performance of the electrode was tested using an electrochemical workstation (CHI660E), including electrochemical impedance spectroscopy and IV curve.

[0103] Electrochemical impedance spectroscopy results ( Fig. 9 a) shows that the polarization resistance of the LPN-SDC reactor at 750°C is 139.9Ωcm 2 , while Ba-doped LPB 0.1 The polarization resistance of the N-SDC reactor is 102.4Ωcm 2 , the polarization resistance is significantly lower than that of undoped ones.

[0104] IV Curve Results( Fig.10 a) shows that the current densities of the LPN-SDC reactor at 750 °C at 1.0, 1.5, and 2.0 V are 13.9, 62.9, and 113.2 mA cm, respectively. -2 , while Ba-doped LPB 0.1 The current densities of the N-SDC reactor at the corresponding voltages were 14.0, 72.1, and 134.7 mA cm -2 .

[0105] Performance test of solid electrolyte reactor in oxygen-containing atmosphere

[0106] The ventilation in the reaction chamber was changed to 1000 ppm NO, 2000 ppm C3H8 and 2.0 vol% O2 gas.

[0107] like Figure 8 As shown, at 2.0V, LPB 0.1 The NO conversion rate of the N-SDC reactor reached 49.9%, which was higher than 46.0% of the LPN-SDC reactor. 0.1The propane conversion of the N-SDC reactor was 96.2%, slightly higher than that of the LPN-SDC reactor at 94.8%.

[0108] Electrochemical impedance spectroscopy results ( Fig. 9 b) shows that the polarization resistance of the LPN-SDC reactor at 750°C is 4.8Ωcm 2 , while the polarization resistance of the product obtained in Example 1 after Ba doping is 3.3Ωcm 2 , the polarization resistance is lower than that of undoped.

[0109] IV Curve Results( Fig.10 b) shows that the current densities of the LPN-SDC reactor at 750 °C at 1.0 and 1.5 V are 106.7 and 148.2 mA cm, respectively. -2 , LPB 0.1 The current densities of the N-SDC reactor at the corresponding voltages were 106.6 and 148.6 mA cm -2 .

Claims

1. A synergistic removal of NO X A solid electrolyte reactor for the treatment of VOCs, characterized by: The invention comprises a solid electrolyte substrate, a cathode located on one side of the solid electrolyte substrate and an anode located on the other side of the solid electrolyte substrate, wherein the cathode and the anode are made of the same material; both the cathode and the anode are porous structures, and both the cathode and the anode contain La 0.5 Pr 1.5-x Ba x NiO4(LPB x N) and Ce 0.8 Sm 0.2 O 1.9 (SDC), where Ce 0.8 Sm 0.2 O 1.9 (SDC) accounts for 30%-40% of the total mass of the two.

2. The synergistic removal of NO according to claim 1 X A solid electrolyte reactor for the treatment of VOCs, characterized by: The cathode and the anode are both made of La 0.5 Pr 1.5-x Ba x NiO4(LPB x N) powder and Ce 0.8 Sm 0.2 O 1.9 (SDC) powder and a binder are made into electrode slurry, and are made on the corresponding side of the solid electrolyte substrate by screen printing.

3. The synergistic removal of NO according to claim 2 X A solid electrolyte reactor for the treatment of VOCs, characterized by: La 0.5 P r1.5-x Ba x NiO4(LPB x N) Powder was prepared by the following method: 1) dissolving La(NO3)3·6H2O, PrN3O9·6H2O, Ba(NO3)2 and Ni(NO3)2·6H2O in distilled water, and controlling the molar ratio of La, Pr, Ba and Ni metal ions to be 0.5:1.5-x:x:1; 2) adding citric acid and ethylenediaminetetraacetic acid to the above solution, controlling the molar ratio of total metal ion: ethylenediaminetetraacetic acid: citric acid = 1:1:1.5; 3) heating in a water bath, adding ammonia water to the solution of step 2) to adjust the pH to 6-8, stirring, and obtaining a wet gel; 4) drying the wet gel in step 3) to obtain a loose and porous dry gel; 5) Calcine the dry gel to obtain La 0.5 Pr 1.5-x Ba x NiO4(LPB x N) powder.

4. The synergistic removal of NO according to claim 2 X A solid electrolyte reactor for the treatment of VOCs, characterized by: Ce 0.8 Sm 0.2 O 1.9 (SDC) powder was prepared by the following method: 1) Dissolve Ce(NO3)3·6H2O and Sm(NO3)3·6H2O in distilled water, and control the molar ratio of Ce and Sm metal ions to be 8:2; 2) adding citric acid and ethylenediaminetetraacetic acid to the above solution, controlling the molar ratio of total metal ion: ethylenediaminetetraacetic acid: citric acid = 1:1:1.5; 3) heating in a water bath, adding ammonia water to the solution to adjust the pH to 6-8, stirring, and obtaining a wet gel; 4) drying the wet gel in step 3) to obtain a loose and porous dry gel; 5) Calcine the dry gel to obtain Ce 0.8 Sm 0.2 O 1.9 (SDC) powder.

5. The synergistic removal of NO according to claim 1 X A solid electrolyte reactor for the treatment of VOCs, characterized by: The solid electrolyte substrate adopts a yttrium stabilized zirconia (YSZ) substrate.

6. A method for synergistically removing NO as claimed in claim 1 X A method for preparing a solid electrolyte reactor for removing pollutants and VOCs, characterized in that: The following steps are included: 1) Preparation of solid electrolyte substrate, La 0.5 Pr 1.5-x Ba x NiO4(LPB x N) powder and Ce 0.8 Sm 0.2 O 1.9 (SDC) powder; 2) preparing electrode slurry from the metal oxide powder in step 1); 3) The electrode slurry in step 2) is made into a cathode attached to one side of the solid electrolyte substrate and an anode attached to the other side by screen printing based on the solid electrolyte substrate to obtain a solid electrolyte reactor.

7. The synergistic removal of NO according to claim 6 X A method for preparing a solid electrolyte reactor for removing pollutants and VOCs, characterized in that: In step 1), the solid electrolyte substrate is prepared by the following method: yttrium stabilized zirconia (YSZ) powder is taken, dry-pressed at a pressure of 180-200 MPa to form an electrolyte green body, and then calcined to obtain a solid electrolyte substrate.

8. The synergistic removal of NO according to claim 6 X A method for preparing a solid electrolyte reactor for removing pollutants and VOCs, characterized in that: In step 1), La 0.5 Pr 1.5-x Ba x NiO4(LPB x N) Powder was prepared by the following method: 1) dissolving La(NO3)3·6H2O, PrN3O9·6H2O, Ba(NO3)2 and Ni(NO3)2·6H2O in distilled water, and controlling the molar ratio of La, Pr, Ba and Ni metal ions to be 0.5:1.5-x:x:1; 2) adding citric acid and ethylenediaminetetraacetic acid to the above solution, controlling the molar ratio of total metal ion: ethylenediaminetetraacetic acid: citric acid = 1:1:1.5; 3) heating in a water bath, adding ammonia water to the solution of step 2) to adjust the pH to 6-8, stirring, and obtaining a wet gel; 4) drying the wet gel in step 3) to obtain a loose and porous dry gel; 5) Calcine the dry gel to obtain La 0.5 Pr 1.5-x Ba x NiO4(LPB x N) powder.

9. The synergistic removal of NO according to claim 6 X A method for preparing a solid electrolyte reactor for removing pollutants and VOCs, characterized in that: In step 1), Ce 0.8 Sm 0.2 O 1.9 (SDC) powder was prepared by the following method: 1) Dissolve Ce(NO3)3·6H2O and Sm(NO3)3·6H2O in distilled water, and control the molar ratio of Ce and Sm metal ions to be 8:2; 2) adding citric acid and ethylenediaminetetraacetic acid to the above solution, controlling the molar ratio of total metal ion: ethylenediaminetetraacetic acid: citric acid = 1:1:1.5; 3) heating in a water bath, adding ammonia water to the solution to adjust the pH to 6-8, stirring, and obtaining a wet gel; 4) drying the wet gel in step 3) to obtain a loose and porous dry gel; 5) Calcine the dry gel to obtain Ce 0.8 Sm 0.2 O 1.9 (SDC) powder.

10. The synergistic removal of NO according to claim 6 X A method for preparing a solid electrolyte reactor for removing pollutants and VOCs, characterized in that: In step 2), the electrode slurry is prepared by the following method: taking La 0.5 Pr 1.5-x Ba x NiO4(LPB x N) powder and Ce 0.8 Sm 0.2 O 1.9 (SDC) powder, Ce 0.8 Sm 0.2 O 1.9 (SDC) powder accounts for 30-40% of the total mass of the two, and a binder is added after grinding; the mass ratio of the total amount of metal oxide powder to the binder is 1:1.5, and continuous grinding is performed to obtain electrode slurry.

Citation Information

Patent Citations

  • LST-SDC-NCAL composite material and application thereof, single-layer fuel cell and preparation method of single-layer fuel cell

    CN111554956A

  • Solid electrolyte battery for removing nitrogen oxides and preparation method thereof

    CN114032557A

  • Two-phase mixed conductor oxygen permeation membrane with stable CO2 as well as preparation method and application of two-phase mixed conductor oxygen permeation membrane

    CN114538915A

  • Potential type gas sensor taking cobalt manganate as sensitive electrode

    CN118376659A

  • Fabrication method of metal supported solid oxide fuel cell

    US20100186220A1